A meteorological study of the sea and land breezes in Bangka Indonesia during the total solar eclipse on March 9, 2016 - Ardi, Nanang Dwi (2018)
Of all mesoscale phenomena, sea and land breezes have been the most studied, both observationally and theoretically. During the total solar eclipse (TSE), some parameters vary anomalously in response to the occurrence of TSE on 9th March 2016 in Bangka, Indonesia. As it occurred during morning hours, it is considered to be much more significant because of its effect in sea and land breezes pattern, especially in term of lag time. We use Portlog Rainwise Automatic Weather Station which is able to measure data in 1 Hz accuracy. Comparison of hourly observations during first contact until final contact result a slow cooling temperature reduction of 0.1°C until totality phase. A significant weakening in wind speed of about 2.5 ms-1 was observed clearly from the instrument. Unfortunately, the reduction is not coincided with the change of wind direction until the third contact. A near constancy in temperature and the wind's behaviour during TSE result delay time in sea and land breezes pattern after the totality. The lag time occurred in three days measurement data, especially sea breeze onset on the next morning day. The lag time in sea breeze was about one hour retardation. The effect of eclipse on the onset timing of sea and land breeze may be attributed to the proportion of heat accumulation due to the obscuration.